Baptism – the Revelation of the Filial Relationship of Christ and the Christian - Kowalski, Marcin (The Biblical Annals, 2021)
The author analyses Jesus’ baptism in Jordan, looking for its parallel in the Christian baptism. He begins by acknowledging the historicity of Jesus’ baptism and reflects on the meaning of the baptism of John by juxtaposing it with similar rites described in the Old Testament texts, in Second Temple Jewish literature, and in rabbinical sources. Then he analyses the meaning of Jesus’ baptism, criticizing the historical-critical interpretations that separate the scene of baptism from the theophany that follows it. According to the author, such an operation is unfounded due to the nature of ancient texts and the literary and thematic continuity between baptism and theophany in the synoptic Gospels. Further, the author presents arguments demonstrating that Jesus comes to Jordan already aware of his identity and mission, which the Father’s voice announces to others and objectivizes. In the last step, it is argued that Jesus’ baptism in Jordan together with the Lord’s death and resurrection could have been a point of reference for the early Christian understanding of baptism connected with the gift of the Spirit, with the filial dignity and the “Abba” prayer and with the inheritance of heaven. All these elements can be found in Rom 8:14-17,23 which describes the new life of those baptized in Christ.